Sex differences in race profile and stroke variables during 200-m sprint in junior kayakers - Hirano, T.; Kashiwagi, Y.; Yamagishi, M.; Senba, S.; Kato, T.; Funato, K. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of present study was to examine sex differences in race profile and stroke variables during 200-m sprint in junior kayakers. 200-m race time of the male kayakers showed 11% shorter than the female kayakers. In both groups, significant positive correlations were found between kayak velocity and stroke rate. In the three part of duration (Initial: 0-25m, Middle: 100-125m, Finish: 175-Zoom), male kayakers were faster than female kayakers. Kayak velocity of male kayakers significantly decreased in the finish part from the middle part, while the kayak velocity of female kayakers showed a most constant. In conclusion, these different raw profiles might be explained by physiological differences in the upper body power or anaerobic capacities between males and females.